Sleep deprivation induces changes in 5-HT actions and 5-HT1A receptor expression in the rat hippocampus. (10th August 2017) - Azizi, H.; Hwang, J.; Suen, V.; Kang, N.Z.; Somvanshi, R.; Tadavarty, R.; Kumar, U.; Sastry, B.R.
Highlights: Sleep deprivation enhances the expression of hippocampal 5-HT1A receptors. 5-HT induced depression of hippocampal CA1 pEPSPs is larger in SD rats. A 24 or 48 h sleep recovery diminished the effect of 5-HT. Abstract: A 12 h sleep deprivation enhances the expression of 5-hydroxytryptamine (5-HT) 1A receptors in rat hippocampus that recedes with 48 h sleep recovery. The depressant effect of applied 5-HT on the field excitatory postsynaptic potentials recorded in the CA1 area, is also enhanced in hippocampi of SD rats. Following a 24 or 48 h sleep recovery, the increase in the 5-HT effect subsided. These results have implications for therapeutics treating clinical depression.